Development Of Denaturing High Performance Liquid Chromatography (Dhplc) In Detection Of Common Polymorphisms In The Multi-Drug Resistance (MDR1) Gene Among Malay Patients With Leukemia [QH324.9.L5 B138 2006 f rb]. - Yahaya, Badrul Hisham (2006)
Although the use of chemotherapy has evolved remarkably during the past 30 years for treatment in leukemia patients, it remains a difficult disease to treat where the main problem is drug resistance. This is due to over expression of multi-drug resistance gene (MDR1) and it’s over expression has been described in many tumors resistant to cytotoxic drugs including leukemias.